Building defect investigation and analysis - Nor Afifah , Zabidi (2012)
Building defects were used to describe imperfections in constructed buildings that can causes inadequacy or failure. This issue may occur due to problems during design stage or construction stage. Building defects not only occur in specific or certain place, but it involves from many different range which are from complex foundation and framing issues to aesthetic issues. The main purpose of this study is identifying types of the building defects, to determine the causes or factors of the building defects and also to analyze appropriate methods and techniques of building maintenance. In this study, the scope will be focusing in Peninsular Malaysia. Questionnaires are distributed to the selected company and also an interview session is conducted with related person on selected company. Data and information are gathered and analyzed using statistical method which is Average Index Percentage using Microsoft Excel. It is found that, twelve (12) defects are identified which are fungus stain and harmful growth, erosion of mortar joint, peeling paint, defective rendering plaster, cracking walls and leaning walls, defective rainwater goods, decayed floorboards, insect or termite attacks, roof defects, dampness penetration through walls, unstable foundations and poor installation of airconditioning units. The factors that cause the defects are climate condition, location of the building, building type and change of use, maintenance approach to the building, building age, support and humidity. There are many methods to maintaining the building. For example, there are six (6) methods for peeling paint defect which are water washing, stream stripping, chemical paint removers, abrasive method, hot air paint stripper and burning off method. To identify those method are very important so that proper maintenance of building can be made and also to avoid defects form repeating.